PENGARUH TRI HITA KARANA TERHADAP KINERJA KARYAWAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING PADA SARASWATI GARMENT - Ni Komang Gita Wahyuni; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (EMAS, 2021)
Employee performance has an important role in achieving company goals. The aims of this study was to explain the effect of Tri Hita Karana on organizational culture and employee performance at Saraswati Garment. This research was conducted at Saraswati Garment using a sample of 75 employees. The sampling technique used was the census method. Data collection was carried out through interviews and questionnaires, with the data analysis techniques used are path analysis techniques. Based on the results of the analysis, this study shows that Tri Hita Karana and organizational culture had a positive and significant effect on employee performance at Saraswati Garment.